The Design and Synthesis of Phenylcyclopropane-Based Secondary Amine Catalysts and Their Applications in Asymmetric Reactions - Takeshima, Aika; Kano, Taichi (Synlett, 2022)
Most chiral secondary amine catalysts are usually synthesized from chiral amino acids and their derivatives. On the other hand, amine catalysts based on a binaphthyl backbone have previously been developed, and show unique chemo- and stereoselectivity in several asymmetric reactions. However, in spite of their utility, the applications of binaphthyl-based amines in asymmetric reactions are still rare due to their synthetic inefficiency. In this context, we have designed amine catalysts possessing a phenylcyclopropane scaffold as a novel chiral motif. These novel catalysts can be synthesized easily and construct a similar chiral environment to that of binaphthyl-based amine catalysts. In addition, a phenylcyclopropane-based amino sulfonamide is found to be an effective catalyst for syn-selective Mannich reactions and conjugate additions using alkynyl Z-ketimines.1 Introduction2 Design and Synthesis of Novel Chiral Secondary Amine Catalysts3 Performance Evaluation of Phenylcyclopropane-Based Amine Catalysts4 Development of Asymmetric Reactions Catalyzed by a Novel Chiral Amino Sulfonamide5 Conclusions
Keywords: amine catalyst; cyclopropane; ketimine; asymmetric reaction; Mannich reaction; conjugate addition